Last words from Montmartre - Qiu, Miaojin 1969-1995; Qiu, Miaojin (New York Review Books, 2014)
"An NYRB Classics Original Last Words from Montmartre is a novel in letters that narrates the gradual dissolution of a relationship between two lovers and, ultimately, the complete unraveling of the narrator. In a voice that veers between extremes, from self-deprecation to hubris, compulsive repetition to sublime reflection, reticence to vulnerability, it can be read as both the author's masterpiece and a labor of love, as well as her own suicide note. Last Words from Montmartre, written just as Internet culture was about to explode, is also a kind of farewell to letters. The opening note urges us to read the letters in any order. Each letter unfolds as a chapter, the narrator writing from Paris to her lover in Taipei and to family and friends in Taiwan and Tokyo. The book opens with the death of a beloved pet rabbit and closes with a portentous expression of the narrator's resolve to kill herself. In between we follow Qiu's protagonist into the streets of Montmartre; into descriptions of affairs with both men and women, French and Taiwanese; into rhapsodic musings on the works of Theodoros Angelopoulos and Andrei Tarkovsky; and into wrenching and clear-eyed outlines of what it means to exist not only between cultures but, to a certain extent, between and among genders. More Confessions of a Mask than Well of Loneliness, the novel marks Qiu as one of the finest experimentalist and modernist Chinese-language writers of our generation"..
Keywords: Epistolary fiction; Love stories; Biographical fiction; FICTION / Biographical; FICTION / Lesbian; FICTION / Psychological; Lesbian authors -- Fiction; Psychological fiction